Do Factors Other than SES Explain Differences in Child Outcomes Between Children of Teenage and Older Mothers for Off-Reserve First Nations Children? - Guèvremont, Anne; Kohen, Dafna (International Indigenous Policy Journal, 2013)
This study used data from the Aboriginal Children’s Survey (ACS) to explore differences in behavioural outcomes for First Nations children born to teen and older mothers living off-reserve in Canada. Of particular interest was an examination of socio-economic and contextual influences, and their contributions to differences in child outcomes. Findings from this study demonstrate that off-reserve First Nations children born to teen mothers (aged 12 - 19 years when they started childbearing) had poorer behavioural outcomes compared to off-reserve First Nations children born to older mothers (aged 25 and over when they started childbearing). These differences were found for emotional symptoms, inattention and hyperactivity, and conduct disorder scores, but not for prosocial behaviours. Contextual factors differed for children born to teen mothers as compared to older mothers, but parenting behaviors and the number of people involved in raising the child was similar for both groups. While differences in the behaviour of children born to teen mothers are often attributed to poorer socio-economic conditions, this study demonstrates that other contextual factors (e.g., breastfeeding, social support, screen time, residential mobility) may be as important as socio-economic factors in their contribution to the behavioural outcomes of children of teen mothers.